Analisis Dampak Sosial dan Ekonomi Pembangunan Infrastruktur di Desa Buntu Tepedo, Kecamatan Sabbang Kabupaten Luwu Utara - Syukri, Muhammad; Baso, Nurfatima Azzahra; Syahdi, Muhammad Zadli (Pascasarjana STIE Amkop Makassar, 2024)
The infrastructure development program aims to overcome accessibility problems and improve the quality of life of people in remote villages. This research focuses on analyzing the social and economic impacts caused by infrastructure development in Buntu Terpedo Village as well as evaluating changes that occur in community welfare. Using a qualitative approach, data collection methods include in-depth interviews with the community, field observations, and focus group discussions (FGD). The research results show that infrastructure development has a significant impact in increasing community mobility, access to education and better health services, as well as encouraging improvements in the local economy which in turn contributes to reducing poverty. However, challenges related to infrastructure management and maintenance as well as obstacles in the level of community participation were also found. This research provides insight into the importance of infrastructure development in accelerating social and economic transformation in rural areas, as well as providing recommendations for sustainable development policies.Keywords : Social Impact, Economic Impact, Infrastructure Development, Equal Development